Feasibility Study of Establishing Diamond and Gemstone Bourse in Thailand - Duangphastra, Chackrit; Boonyanet, Wachira (Arts of Management Journal, 2024)
This article aimed to: 1) study significant conditions impacting the operations of the organized market and the best practices of various countries in managing diamond and gemstone bourses. 2) conduct a feasibility study of establishing diamond and gemstone bourses in Thailand, and 3) propose a driving plan to develop diamond and gemstone bourses in Thailand. This research used qualitative methods and content analysis by collecting data from field surveys in Thailand and overseas and arranging focus groups comprising representatives from relevant private and public sectors to obtain a common conclusion. The research result found that Thailand has great potential to develop the diamond bourse, especially in Bangrak District, by differentiating itself from other bourses by offering trading of certified and origin-proven diamond and colored stones, arranging auctions in controlled security systems, recording incoming and outgoing tradable products, and taxing properly remitting them, and having good governance, as well as having government agencies related to trading and trade facilitation stationed in the established bourse. Revenues earned from managing bourses are generated from membership fees, commission fees from diamond and gemstone auctions, training, and other marketing promotion activities. Driving the establishment of diamond and gemstone bourses in Thailand requires the support of the Ministry of Commerce and the World Federation of Diamond Bourses.